Financial intelligence for entrepreneurs : what you really need to know about the numbers - Berman, Karen, 1962-; Knight, Joe, 1963-; Case, John, 1944-; Berman, Karen, 1962- (Boston, Mass. : Harvard Business Press, 2008)
"In this essential guide, Karen Berman and Joe Knight customize the approaches and insights from their acclaimed book Financial Intelligence specifically for entrepreneurs. The authors not only demystify common financial terms and tools, they also show how you can use this knowledge to gauge your company's performance and make better decisions."-back cover.
Preface : what this book is about -- pt. 1. The art of finance (and why it matters) -- 1. What is financial intelligence? -- 2. A primer on the art of finance -- Part one toolbox : financing your business ; Building a financial staff -- pt. 2. The (many) peculiarities of the income statement -- 3. Profit is an estimate -- 4. Cracking the code of the income statement -- 5. Revenue : the issue is recognition -- 6. Costs and expenses : no hard-and-fast rules -- 7. The many forms of profit -- Part two toolbox : understanding variance ; Calculating percent of and percent change -- pt. 3. The balance sheet reveals the most -- 8. Understanding balance sheet basics -- 9. Assets : more estimates and assumptions (except for cash) -- 10. On the other side : liabilities and equity -- 11. Why the balance sheet balances -- 12. The income statement affects the balance sheet -- Part three toolbox : employees as assets ; Expense vs. capital expenditure -- pt. 4. Cash is king -- 13. Cash is a reality check -- 14. Profit [does not equal] cash (and you need both) -- 15. The language of cash flow -- 16. How cash connects with everything else -- 17. Why cash matters -- Part four toolbox : cash accounting ; Free cash flow -- pt. 5. Ratios : learning what the numbers are really telling you -- 18. The power of ratios -- 19. Profitability ratios : the higher the better (mostly) -- 20. Leverage ratios : the balancing act -- 21. Liquidity ratios : can we pay our bills? -- 22. Efficiency ratios : making the most of your assets -- Part five toolbox : which ratios are most important? ; The power of percent of sales ; Sustainable growth rate -- pt. 6. How to calculate (and really understand) return on investment -- 23. The Building Blocks of ROI -- 24. Figuring ROI : the nitty-gritty -- Part six toolbox : a step-by-step guide to analyzing capital expenditures -- pt. 7. Applied financial intelligence : working capital management -- 25. The magic of managing the balance sheet -- 26. Your balance
Rev. ed. of: Financial intelligence. 2006.
Includes bibliographical references (pages [263]-264) and index.
Description based on print version record.
Keywords: Financial statements; Cash management; Business enterprises -- Finance; Corporations -- Finance; Finanzierung; Finanzwirtschaft; Jahresabschluss; Betriebliche Finanzwirtschaft; Entrepreneurship-Ansatz; Spojené státy americké; Business enterprises -- Finance; Cash management; Corporations -- Finance; Financial statements; BUSINESS & ECONOMICS / Industrial Management; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Organizational Behavior; elektronické knihy; electronic books